2013
DOI: 10.1159/000350483
|View full text |Cite
|
Sign up to set email alerts
|

Relapse (Number of Detoxifications) in Abstinent Male Alcohol-Dependent Patients as Related to Personality Traits and Types of Tolerance to Frustration

Abstract: Background: Personality traits like depression on the one hand and aggression and impulsivity on the other are assumed to be predisposing factors for different types of alcohol dependence. Both types are associated with sensitivity to frustration, but this may be different for the two types of personality according to whether they are confronted with frustrations caused by withdrawal from positive or infliction of negative events. It has not been shown so far if both types of personality factors and the two di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 40 publications
1
21
0
2
Order By: Relevance
“…In addition to violence, high emotional reactivity during sustained abstinence may be a large contributing factor to relapse, in heavy binge-drinking adolescents (Winward et al 2014). Relapse was most highly correlated with aggression, more so than with impulsivity, anxiety, and depression in abstinent male alcoholics (Baars et al 2013). We report that high proportions of mice show aggression during withdrawal from 8 wks EtOH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to violence, high emotional reactivity during sustained abstinence may be a large contributing factor to relapse, in heavy binge-drinking adolescents (Winward et al 2014). Relapse was most highly correlated with aggression, more so than with impulsivity, anxiety, and depression in abstinent male alcoholics (Baars et al 2013). We report that high proportions of mice show aggression during withdrawal from 8 wks EtOH.…”
Section: Discussionmentioning
confidence: 99%
“…Features of EtOH withdrawal can include dysfunctional social and aggressive behavior (Broadwater et al 2011; Overstreet et al 2002; Varlinskaya and Spear 2004), in addition to common symptoms such as headaches, fever, convulsions, and anxiety (Trevisan et al 1998). Experimental studies examining either recovering alcoholics or heavy, binge-drinking youths independently link greater increases in frustration and irritability during early abstinence to a higher chance of relapse (Baars et al 2013; Winward et al 2014). It would be beneficial to identify a translational model of EtOH withdrawal-induced aggression.…”
mentioning
confidence: 99%
“…Aggression is a common behavioral correlate of ethanol withdrawal in rodents (e.g., Hwa et al, 2015) and the present findings are consistent with this given that aggression was the most prominent withdrawal symptom observed, though other common motor abnormalities were observed. Baars et al (2013) have reported that aggression is highly correlated with mood disorders and risk of relapse in a sample of male alcohol-dependent patients. The present findings also demonstrated that ORG 34517 attenuated increases in CORT plasma levels during the third withdrawal period from the chronic, intermittent intoxication regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Although minimally studied empirically to assess effects on substance use, frustration is one common type of stressor frequently reported to occasion problematic drinking in humans (Baars, Müller, Gallhofer, & Netter, 2013;Miller, 1991). Operationally, frustrations are events during which previous contingencies cease to produce expected reinforcement (Amsel, 1958;Skinner, 1950).…”
mentioning
confidence: 99%